VALIDITY AND RELIABILITY THE INSTRUMENT OF MODEL KEUSAHAWANAN PELAJAR UNIKL (KPU) USING THE RASCH MEASUREMENT MODEL - Siti Noor Kamariah Yaakop; Nooraini Othman; Wardatul Aishah Musa (Marine Frontier, 2020)
The University of Kuala Lumpur (UniKL) has developed the Entrepreneurship Syllabus as a compulsory course along with the TeknoputraTM Development Program (TDP) to foster entrepreneurial tendencies among students, in line with its mission to globally produce technical entrepreneurs. A research was conducted to identify factors that could affect student entrepreneurial tendenciesthrough the Entrepreneurship Development Program. The purpose of this study is to evaluate the validity and reliability of the newly developed instrument, namely the model Kecenderungan Pelajar UniKL (KPU). This quantitative analysis was carried out at the UniKL Malaysian Institute of Marine Engineering Technology (MIMET). Data analysis using Winstepsshowed that the person fit value was 0.95 and the item reliability was 0.70. The Cronbach Alpha value is 0.99. The separation value of the person was 4.36 and the separation value of the item was 1.52. Over 12 items have been dropped, the item reliability seen increasingfrom 0.70 to 0.73. Meanwhile, the Cronbach Alpha (KR-20) remained at 0.99.While there is a slight decrease in variance explain by measure, the variance value is still within the range of 40%. Therefore the study of the item validity and reliability of ModelKPUcomplied with the standardsreferred to the experts and the Rasch Measurement Model.